การบริหารศูนย์ศึกษาพระพุทธศาสนาวันอาทิตย์ในรูปลักษณ์ใหม่ - ม่วงศรี สุฉิรา; ศิริภิรมย์ อ.ดร.วลัยพร (An Online Journal of Education, 2015)
การวิจัยครั้งนี้ เป็นการวิจัยเชิงสำรวจ โดยการวิจัยนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาสภาพปัจจุบันและสภาพที่พึงประสงค์ในการบริหารศูนย์ศึกษาพระพุทธศาสนาวันอาทิตย์ในรูปลักษณ์ใหม่ 2) เพื่อหาแนวทางการบริหารศูนย์ศึกษาพระพุทธศาสนาวันอาทิตย์ในรูปลักษณ์ใหม่ ผลการวิจัยพบว่าผู้ตอบแบบสอบถามส่วนใหญ่เป็นชายร้อยละ 66.00 วุฒิการศึกษาระดับปริญญาโทมากที่สุด อายุ 51 ปีขึ้นไปมากที่สุด ประสบการณ์การดำรงตำแหน่งปัจจุบันในศูนย์ศึกษาพระพุทธศาสนาวันอาทิตย์ 6–10 ปีมากที่สุด ผู้ตอบแบบสอบถามส่วนใหญ่เป็นครูผู้สอน สภาพปัจจุบันของการการบริหารศูนย์ศึกษาพระพุทธศาสนาวันอาทิตย์ในรูปลักษณ์ใหม่ในภาพรวมอยู่ในระดับมา (x̄ = 3.99) พิจารณารายด้านพบว่า ทุกด้านอยู่ในระดับมากเช่นเดียวกัน ด้านที่มีค่าเฉลี่ยสูงที่สุดคือด้านการรักษาวัฒนธรรมไทย (x̄ = 4.28) รองลงมาคือด้านการฟื้นฟูบทบาทวัด (x̄ = 4.16) ส่วนด้านที่ค่าเฉลี่ยต่ำที่สุดคือด้านการบริหารแบบมีส่วนร่วม (x̄ = 3.64) สภาพที่ พึงประสงค์ของการบริหารศูนย์ศึกษาพระพุทธศาสนาวันอาทิตย์ในรูปลักษณ์ใหม่ในภาพรวมอยู่ในระดับมาก (x̄ = 4.17) เมื่อพิจารณารายด้าน พบว่าทุกด้านอยู่ในระดับมากเช่นเดียวกัน ด้านที่ค่าเฉลี่ยสูงที่สุดคือ ด้านการรักษาวัฒนธรรมไทย (x̄ = 4.40) รองลงมาคือด้านการฟื้นฟูบทบาทวัด (x̄ = 4.31) และด้านการบริหารแบบมุ่งเน้นคุณภาพ (x̄ = 4.12) ส่วนด้านที่มีค่าเฉลี่ยต่ำที่สุดคือด้านการบริหารแบบมีส่วนร่วม (x̄ = 3.95) ผลการจัดลำดับความต้องการจำเป็นของการบริหารศูนย์ศึกษาพระพุทธศาสนาวันอาทิตย์ในรูปลักษณ์ใหม่ในภาพรวม พบว่า ด้านที่มีค่าดัชนีความต้องการจำเป็นสูงสุด ได้แก่ ด้านการบริหารแบบมีส่วนร่วม (PNIModified = 0.086) รองลงมาคือ ด้านการตัดสินใจด้วยตนเองของชุมชน (PNIModified = 0.064) ส่วนด้านที่มีค่าดัชนีความต้องการจำเป็นต่ำที่สุด คือ ด้านการรักษาวัฒนธรรมไทย (PNIModified = 0.029) The research is a survey Research. The aim of the research were 1) to study present state and desirable state of The New Image Administration Sunday Buddhist Study Center, and 2) to find the administration method of The New Image Administration Sunday Buddhist Study Center. The research’s result were: Most of samples are male, 66% of master’s degree, age above 51 years, 6-10 years of present position’s experience in The Sunday Buddhist Study Center and the most of answerer were instructor . The overall image of average of present states of The New Image Administration Sunday Buddhist Study Center was in great level (x̄ = 3.99, SD). When consider in particular, The greatest average was in the preserve Thai culture (x̄ = 4.28) following to the temple role’s recovery (x̄ = 4.16) and the administration of participation and total quality management (x̄ = 4.00). The average of the administration of participation management were at the least (x̄ = 3.64). The overall image of average of desirable state of The New Image Administration Sunday Buddhist Study Center was in great level (x̄ = 4.17). When consider in particular, The greatest average was in the preserve Thai culture (x̄ = 4.40) following to the temple role’s recovery (x̄ = 4.31) and the administration of total quality management (x̄ = 4.12). The average of the administration of participation management were at the least (x̄ = 3.95). A comparison of priority needs of The New Image Administration Sunday Buddhist Study Center : the greatest priority needs index was the administration of participation management (PNIModified = 0.086) following to the self-decision-making of community (PNIModified = 0.064) and the temple role’s recovery (PNIModified = 0.036). The priority needs index of the preserve Thai culture were at the least (PNIModified = 0.029).